Prediction of Unbound Vancomycin Levels in Intensive Care Unit and Nonintensive Care Unit Patients: Total Bilirubin May Play an Important Role - Li X; Xu W; Li R; Guo Q; Li X; Sun J; Sun S; Li J (Infection and Drug Resistance, 2021)
Xiao Li,1,* Wen Xu,1,* Ran Li,2 Qie Guo,1 Xiangpeng Li,1 Jialin Sun,1 Shuhong Sun,1 Jing Li1 1Department of Clinical Pharmacy, The Affiliated Hospital of Qingdao University, Qingdao, Shandong, 266003, People’s Republic of China; 2Department of Infectious Diseases, The Affiliated Hospital of Qingdao University, Qingdao, Shandong, 266003, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiao Li; Jing LiDepartment of Clinical Pharmacy, The Affiliated Hospital of Qingdao University, 16 Jiangsu Road, Qingdao, Shandong, 266003, People’s Republic of ChinaTel/Fax +86-53-82912263Email lixiaoxiao0413@163.com; lijing7112@126.comBackground: The mean unbound vancomycin fraction and whether the unbound vancomycin level could be predicted from the total vancomycin level are still controversial, especially for patients in different groups, such as intensive care unit (ICU) versus non-ICU patients. Other relevant potential patient characteristics that may predict unbound vancomycin levels have yet to be clearly determined.Methods: We enrolled a relatively large study population and included widely comprehensive potential covariates to evaluate the unbound vancomycin fractions in a cohort of ICU (n=117 samples) and non-ICU patients (n=73 samples) by using a liquid chromatography-tandem mass spectrometry (LC-MS/MS) method.Results: The mean unbound vancomycin fraction was 45.80% ± 18.69% (median, 46.01%; range: 2.13– 99.45%) in the samples from the total population. No significant differences in the unbound vancomycin fraction were found between the ICU patients and the non-ICU patients (P=0.359). A significant correlation was established between the unbound and total vancomycin levels. The unbound vancomycin level can be predicted with the following equations: unbound vancomycin level=0.395×total vancomycin level+0.019×total bilirubin level+0.468 (R2=0.771) for the ICU patients and unbound vancomycin level=0.526×total vancomycin level-0.527 (R2=0.749) for the non-ICU patients. Overall, the observed-versus-predicted plots were acceptable.Conclusion: A significant correlation between the total and unbound vancomycin levels was found, and measurement of the unbound vancomycin level seems to have no added value over measurement of the total vancomycin level. The study developed parsimonious equations for predicting the unbound vancomycin level and provides a reference for clinicians to predict the unbound vancomycin level in adult populations.Keywords: unbound vancomycin fraction, unbound vancomycin level, patient characteristics, predictors